Layanan Konseling dalam Mereduksi Kecemasan Belajar melalui Pendekatan Eksistensial Humanistik - Zulfikri, Zulfikri; Amirullah, M; Aswar, Aswar; Fitriana, Fitriana (Universitas Negeri Makassar, 2022)
Learning anxiety is a feeling that arises when a person is unable to control himself or is helpless in certain circumstances. Usually, people who experience anxiety have several reactions, such as a racing heart, tension, and even emotion. anxiety becomes an obstacle in the learning process that can reduce the performance of a person's cognitive functions, such as in concentrating, remembering, forming concepts and solving problems. The humanistic existential approach is a theory that focuses on the human condition which focuses on an attitude that emphasizes an understanding of humans. The existential approach also directs individuals to become more aware that they have the freedom to choose and act, and then helps them make life choices that enable them to actualize themselves and achieve a meaningful life. Existential therapy can help counselees to be able to deal with the anxiety of choosing for themselves and then accept the reality that they are more than just victims of the power of determining outside themselves.